Assignment on Path Models - Haque, M. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Based on your reading of the text, the corresponding class lectures and discussion of the materials from Chapter 1: The Outcomes of Organizations, provide a written response to the following questions.